Comparison of high-impact load-absorbing property of natural turf for professional use with various types of natural and artificial turfs in football. (December 2019) - Nunome, Hiroyuki; Inoue, Koichiro; Ball, Kevin; Sano, Shinya; Ikegami, Yasuo
The present study aimed to illustrate load stress-strain properties of various types of natural and artificial turfs. A modified high-loading test rig was used to measure shock absorbency and concurrent deformation of these surfaces in situ to calculate quasi stress-strain curves. A natural turf professionally maintained for top professional league soccer matches (N-stadium) was used as the reference surface. Other surfaces included two natural turfs without professional maintenance (one with and one without polyethylene pile reinforcement), four new artificial turfs (sand infill only, rubber infill only, both sand and rubber, and thermoplastic elastomer infill), and one aged artificial turf (8 years old with sand/rubber infill). All artificial turfs failed to mimic two properties of N-stadium, plastic deformation, and hysteresis profile, suggesting N-stadium has more energy absorbable properties than those of artificial turfs. The aged artificial turf with conventional infill was substantially stiffer than the new artificial turf with the same infill, indicating age affects the stiffness of these surfaces. Also, distinctive differences were detected between N-stadium and other natural turfs, suggesting factors such as daily maintenance work are very influential on their quasi stress-strain properties. Interestingly, no difference in the quasi stress-strain curve existed between the natural turf with and without polyethylene pile reinforcement. While artificial surfaces are improving, there is still a difference in properties between these surfaces and natural turf pitches.